2017
DOI: 10.1111/jpy.12586
|View full text |Cite
|
Sign up to set email alerts
|

Both modular and single‐domain Type I polyketide synthases are expressed in the brevetoxin‐producing dinoflagellate, Karenia brevis (Dinophyceae)

Abstract: Dinoflagellates are prolific producers of polyketide compounds, many of which are potent toxins with adverse impacts on human and marine animal health. To identify polyketide synthase (PKS) genes in the brevetoxin‐producing dinoflagellate, Karenia brevis, we assembled a transcriptome from 595 million Illumina reads, sampled under different growth conditions. The assembly included 125,687 transcripts greater than 300 nt in length, with over half having >100× coverage. We found 121 transcripts encoding Type I ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 67 publications
(78 reference statements)
7
43
0
Order By: Relevance
“…Variations of the GYLG motif (DYLG, HYLG, YYLG, GLLG, AYLG and ALLG) were also observed in this study in the four transcriptomes and have been also been reported from previous dinoflagellate libraries (Monroe and Van Dolah, ; Eichholz et al ., ; Pawlowiez et al ., ; Meyer et al ., ; Van Dolah et al ., ) (Fig. ).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Variations of the GYLG motif (DYLG, HYLG, YYLG, GLLG, AYLG and ALLG) were also observed in this study in the four transcriptomes and have been also been reported from previous dinoflagellate libraries (Monroe and Van Dolah, ; Eichholz et al ., ; Pawlowiez et al ., ; Meyer et al ., ; Van Dolah et al ., ) (Fig. ).…”
Section: Discussionmentioning
confidence: 93%
“…Our KS phylogenetic tree reports similar evolutionary trends compared to previous studies, such as the three iterative dinoflagellate sub‐clades amongst the ‘protistan’ clade and numerous multiple (modular) KS domains, with the addition of NRPS/PKS hybrid clades that are closely related to bacterial type I PKS clade (Monroe and Van Dolah, ; López‐Legentil et al ., ; Eichholz et al ., ;Kohli et al ., ; Van Dolah et al ., ). All single KS domain identified in this study from the four dinoflagellate species belonged to either one of the three protistian sub‐clades that have been previously described suggesting that these single domain transcripts are of dinoflagellate origin and not due to bacterial and fungal contaminations in the cultures.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Murray and co‐workers revealed the most comprehensive collection of polyketide synthase genes in dinoflagellates so far from the genomes of Gambierdiscus polynesiensis and Gambierdiscus excentricus , some of which could be associated with the production of ciguatoxins . Concurrently, Murray and co‐workers published a transcriptome from K. brevis which revealed several single and multidomain polyketide synthases potentially involved in the production of brevetoxins . This cutting edge work by Murray provides new clues toward understanding the enzymes involved in assembling the complex polyether ladder scaffolds.…”
Section: Receptor Site Vmentioning
confidence: 99%
“…[80] Concurrently, Murray andc o-workersp ublished at ranscriptome from K. brevis which revealed several single and multidomainp olyketide synthases potentially involved in the production of brevetoxins. [82] This cutting edge work by Murray provides new clues toward understanding the enzymes involvedi na ssembling the complex polyether ladder scaffolds.…”
Section: Brevetoxins and Ciguatoxinsmentioning
confidence: 99%